Respuesta :
(24+2)+2=28.
First, you work with the parentheses. (24+2)=26. So now your expression is 26+2. Lastly, you solve the expression. 26+2=28.
First, you work with the parentheses. (24+2)=26. So now your expression is 26+2. Lastly, you solve the expression. 26+2=28.
Answer:
[tex]\boxed{=28}[/tex]
Step-by-step explanation:
This question is about pemdas.
P-Parenthesis
E-Exponents
M-Multiply
D-Divide
A-Add
S-Subtract
First, calculate parenthesis, and add from left to right.
(24+2)+2
24+2=26
26+2=28
Final answer: =28
Hope this helps!
And thank you for posting your question at here on brainly.
Have a great day!
-Charlie